2019
DOI: 10.1519/jsc.0000000000002404
|View full text |Cite
|
Sign up to set email alerts
|

Training Load, Physical Performance, Biochemical Markers, and Psychological Stress During a Short Preparatory Period in Brazilian Elite Male Volleyball Players

Abstract: The aim of this study was to assess the relationship between training load (TL) and physical performance, biochemical markers, and psychological stress during a short preparatory period (PP) in Brazilian elite male volleyball players. Twelve volleyball players from a team competing in the Brazilian Men's Volleyball Super League were enrolled (26.9 ± 4.6 years). Countermovement Jump (CMJ), Creatine Kinase (CK), Testosterone (T), Cortisol (Cr), T/Cr ratio, and Recovery and Stress Questionnaire for Athletes (REST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
2
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 42 publications
5
58
2
12
Order By: Relevance
“…Regarding the load values found in other studies with volleyball athletes, only one was similar to the values found in this study, with values ranging from 4138±664 to 4427±409 U.A during two weeks of intensification of training loads. 15 In the study by Horta et al 16 , the load values found during the preparatory period were higher (5942±962 U.A) compared to our study.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Regarding the load values found in other studies with volleyball athletes, only one was similar to the values found in this study, with values ranging from 4138±664 to 4427±409 U.A during two weeks of intensification of training loads. 15 In the study by Horta et al 16 , the load values found during the preparatory period were higher (5942±962 U.A) compared to our study.…”
Section: Discussioncontrasting
confidence: 59%
“…[10][11][12][13] The tools used to assess recovery include the Total Quality Recovery (TQR) scale and the Well--Being Questionnaire (WB). 2,11 Although some studies monitor training loads in volleyball at some points during the season, [14][15][16] there is still a lack of studies on the recovery state behavior along the season, of how the characteristics of some periods will influence it to help understand the recovery and its variables in volleyball.…”
Section: Introductionmentioning
confidence: 99%
“…Serum CK and LDH levels may be increased due to skeletal muscle damage as a consequence of intense training and are directly associated with training load ( Horta et al, 2017 ). In addition, muscle damage can induce delayed-onset muscle soreness and performance loss ( Peake and Neubauer, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The success of training, in turn, depends on the balance between training load magnitude and recovery. 1,[5][6][7] In recent decades, the session rating of perceived exertion (RPE) method 8,9 has proved to be a simple and very useful tool for quantifying and monitoring volleyball training loads, 1,2,5,[10][11][12][13][14] indicating good applicability of the method in elite volleyball teams. The RPE represents a subjective parameter of measurement after the exercise session that reflects the integration between the central and peripheral signals, with a repercussion on efferent neural impulses from the motor cortex, generated and memorized in the central nervous system, interpreted by the sensory cortex, producing a general or local perception of the effort required to accomplish a particular task.…”
Section: Introductionmentioning
confidence: 99%